2011
DOI: 10.1186/1750-1172-6-11
|View full text |Cite
|
Sign up to set email alerts
|

Mortality associated with neurofibromatosis type 1: A study based on Italian death certificates (1995-2006)

Abstract: BackgroundPersons affected by neurofibromatosis type 1 (NF1) have a decreased survival, yet information on NF1-associated mortality is limited.Methods/AimThe National Mortality Database and individual Multiple-Causes-of-Death records were used to estimate NF1-associated mortality in Italy in the period 1995-2006, to compare the distribution of age at death (as a proxy of survival) to that of the general population and to evaluate the relation between NF1 and other medical conditions by determining whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 29 publications
3
42
0
1
Order By: Relevance
“…The overwhelming characteristic feature of NF1 is peripheral nerve sheath tumors (neurofibromas, malignant peripheral nerve sheath tumors [MPNST]), which form as a result of the loss of the tumor suppressor protein neurofibromin 3–6. MPNST are a major cause of reduced life expectancy in NF1 patients 5,7,8…”
Section: Neurofibromatosis (Type 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…The overwhelming characteristic feature of NF1 is peripheral nerve sheath tumors (neurofibromas, malignant peripheral nerve sheath tumors [MPNST]), which form as a result of the loss of the tumor suppressor protein neurofibromin 3–6. MPNST are a major cause of reduced life expectancy in NF1 patients 5,7,8…”
Section: Neurofibromatosis (Type 1)mentioning
confidence: 99%
“…To date, a number of studies have examined the impact of these diseases (mainly focusing on the most common of these conditions [eg, neurofibromatosis]) and postsurgical survival 15. The number of studies which investigate the full effect of hereditary diseases that predispose to early-onset tumors upon life expectancy remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Neurofibromatosis type I (NF1) or von Recklinghausen disease is an autosomal dominant disorder affecting one in 3,000 individuals [1]. Typically, the disease is diagnosed clinically during childhood, as the first sign in 80% of NF1 individuals is usually café-au-lait macules by 1 year of age.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple neurofibromatosis is an autosomal dominant disorder with an incidence of approximately one in 3,000 live births [1]. The gene locus of neurofibromatosis is characteristically localized to a chromosome 17.…”
Section: Introductionmentioning
confidence: 99%
“…Some cohort studies have reported a mean reduction of 8 to 15 years 4,5 while studies based on death certificates have shown a greater reduction (of about 16 to 20 years) 6,7 in life expectancy. The leading reported cause of early death in all age groups is malignant neoplasm, especially malignant peripheral nerve sheath tumor (MPNST).…”
Section: Mortality and Associated Conditionsmentioning
confidence: 99%